Mass poisonings of the Vulnerable Andean condor prompt national strategy against the use of toxic baits in Argentina - Jácome, N. Luis; Abarzua, Gabriela; Astore, Vanesa; Estrada Pacheco, Rayen (Ethnobiology and Conservation, 2022)
Massive deaths of Andean condors (Vultur gryphus) prompted a National Strategy Against the Use of Toxic Baits in Argentina, based on 6 lines of action: 1) delivery of kits and uniﬁed intervention protocols in cases of wildlife poisoning, 2) community education programs, 3) surveys of rural people, 4) training courses and participatory construction workshops, 5) toxicology studies, and 6) an academic-scientiﬁc committee made up of specialists in toxicology. The strategy was developed in the 14 provinces of the country where the Andean condor is distributed. 554 people from 166 institutions have participated in the trainings and workshops, reporting 200 poisoning events involving more than 21000 individuals from 61 species. Birds and mammals were the groups most aﬀected, and further, human victims show the impact on public health. 19 toxic substances were identiﬁed, mainly insecticides. This study proved that carbofuran is the toxic most used. Analysis of bait types suggests a signiﬁcant conﬂict with carnivores. 195 surveys revealed that almost half of the farmers know people who use toxic baits and that the negative perception towards some species could determine their use. The strategy began to address the problem of the use of toxic baits in Argentina in a strategic, participatory and regional way, through the management of public policies and scientiﬁc research. We propose actions to work on the causes that lead to the application of this dangerous practice. Given its extensive use, we believe that this strategy can be adapted and applied in other countries in the region.